THE IMPLEMENTATION POLICY OF THE MERDEKA CURRICULUM IN ELEMENTARY SCHOOLS, CLUSTER 1 LABUHAN HAJI DISTRICT, EAST LOMBOK REGENCY - Atiaturrahmaniah Atiaturrahmaniah; I Wayan Lasmawan; I Wayan Suastra; Muh. Yazid (PIONIR: JURNAL PENDIDIKAN, 2023)
AbstractThis article examines the implementation, support, and challenges faced in adopting and implementing the Merdeka Curriculum in Cluster 1 elementary schools in Labuhan Haji District, East Lombok Regency. The Merdeka Curriculum is a new educational framework in Indonesia aimed at addressing the learning crisis and empowering schools with autonomy and independence in determining teaching and learning approaches. The study employs qualitative descriptive research, utilizing observation, interviews, and documentation as data collection techniques. The findings reveal that SDN 4 Labuhan Haji, as a pioneering school, has implemented the Merdeka Curriculum through intracurricular, co-curricular, and extracurricular activities. However, the other five schools are still using a "self-learning" option. The understanding of teachers and support from the local Department of Education have been crucial in facilitating the implementation of the curriculum. Nevertheless, challenges such as low teacher commitment, limited instructions and policies, inadequate access to funds, and technological proficiency hinder the effective implementation of the Merdeka Curriculum. The study provides insights into the implementation process, government support, and obstacles encountered, contributing to a better understanding of the Merdeka Curriculum in elementary